Sociology of education in India: Changing contours and emerging concerns - Nambissan, Geetha B; Nambissan, Geetha B; Rao S. Srinivasa (New Delhi Oxford University Press, 2013)
The "Sociology of Education in India: Changing Contours and Emerging Concerns" examines the trajectory of the Sociology of Education (SoE) in India, focusing on how factors like structural inequalities, poverty, cultural diversity, and identity influence the education system. The volume highlights the need to develop a stronger "sociological imagination" to understand education's role as a social institution, address the challenges within the Indian education system, and fill gaps in foundational reading material on the subject in the country. Key issues explored include equality, identity, exclusion, and the intersection of education with the world of work.
Keywords: Educational sociology--India